Becoming more systematic about flexible learning: beyond time and distance - Wim De Boer; Betty Collis (Association for Learning Technology, 2005)
Changes in higher education frequently involve the need for more flexibility in course design and delivery. Flexibility is a concept that can be operationalized in many ways. One approach to conceptualizing flexibility within courses is to distinguish planning-type flexibility, which the instructor can designate before the course begins and which needs to be managed when the course is offered, for interpersonal flexibility, which relates more to the dynamics of the course as it is experienced by the learners. Course management systems (CMSs) offer options that can support both of these sorts of flexibility, if instructors use the CMSs with a systematic frame of reference. The instructor faces challenges in managing both types of flexibility, but the experience at one institution shows that being systematic about flexibility choices and ways to support those choices in the institutional CMS can help in meeting these challenges.